PENINGKATAN KOMPETENSI SISWA MELALUI PEMBINAAN BENGKEL SHALAT DAN LABORATORIUM AL-QUR’AN DI MADRASAH ALIYAH NEGERI (MAN) 2 PAMEKASAN - Wafa, Ali (Fakultas Agama Islam Universitas Islam Madura, 2019)
Teaching is not only the transfer of knowledge to students but also how teachers are able to guide and guide the material that students receive coloring their behavior in daily life. This study used a descriptive qualitative approach because this approach is relevant to be used to gain an in-depth understanding of prayer workshop and the Koran laboratory. The method is used in collecting data are observation, interviews and documentation. The purpose of this study was to find out: (1) the steps is taken by the head of MAN 2 Pamekasan in improving student competence through prayer workshop and al-Qur'an laboratory development; (2) the role of the teacher in improving student competence through prayer workshop and al-Qur'an laboratory development in MAN 2 Pamekasan; and (3) supporting factors and in improving student competence. Research results: (1) steps is taken by the principal; a) conduct teacher training; b) learning methods vary; c) complete facilities: 2) teacher's role in fostering students; a) prayer formation; b) teaching guidance; c) moral guidance: 3) supporting factors; a) teacher factor; b) student factors; and c) facility factors.